The Lebanese Cannabis Oil Extract promotes resilience to Chronic Social Defeat in C57BL/6J male mice - Mezher, Amar (2022)
Major Depressive Disorder (MDD) has become one of the most common mental disorders around the world. Although antidepressants remain the first-line treatment for moderate to major depression, however, numerous limitations have been reported regarding their efficacy and long-term side effects. Cannabis sativa is the most common type of Cannabis which is being extensively used for medical purposes. Conflicting results are reported regarding the effects of Cannabis on depression and anxiety. As a result, more studies are needed to understand how Cannabis affect these behaviors. Therefore, the aim of this study was to investigate the therapeutic effect of the Lebanese Cannabis Oil Extract (COE) in the context of depression and anxiety-like behaviors in C57BL/6J male mice using the Chronic Social Defeat Stress protocol (CSDS). The cotreatment paradigm was applied in order to examine the COE effects when given as a prophylactic treatment, along with stress induction. In a post paradigm, the antidepressant and anxiolytic effects of the COE were assessed after stress induction. In both paradigms, experimental mice received either 20mg/kg, 5mg/kg or 1mg/kg of COE through intraperitoneal injections. Control mice received injections of vehicle solution. Following every treatment, the social interaction test was used to assess depression-like behaviors and social avoidance, whereas elevated plus maze test was used to assess the anxiety-like behaviors in mice. We found out that the highest dose of COE promoted resilience to chronic social defeat stress and rescued depression- like behaviors, however turned out to be anxiogenic when given as a preventative treatment. the 5mg/kg dose showed positive effects on promoting resilience to stress and rescuing depression-like behaviors in mice with no particular effect on anxiety-like behaviors. The lowest dose turned out to be anxiogenic when given in a preventative treatment without any particular effect on depression-like behaviors in both paradigms. In conclusion, according to the behavioral outcomes of treated mice, the Lebanese COE showed antidepressant properties without affecting anxiety. Further investigations are needed to identify the molecular pathways by which COE exerts its positive effects.